What do hospital consultants value about their jobs? A discrete choice experiment. Issue 7404 (25th June 2003) - Ubach, Cristina; Scott, Anthony; French, Fiona; Awramenko, Morag; Needham, Gillian
Abstract: Objective To examine the strength of hospital consultants' preferences for various aspects of their work. Design Questionnaire survey including a discrete choice experiment. Setting NHS Scotland. Participants 2923 hospital consultants in Scotland. Main outcome measures Monetary valuations or prices for each job characteristic, based on consultants' willingness to pay and willingness to accept extra income for a change in each job characteristic, calculated from regression coefficients. Results The response rate was 61% (1793 resspondents). Being on call was the most important attribute, as consultants would need to be compensated up to £18 000 (30% of their average net income) (P < 0.001) for a high on-call workload. Compensation of up to £9700 (16% of their net income) (P < 0.001) would be required for consultants to forgo opportunities to undertake non-NHS work. Consultants would be willing to accept £7000 (12% of net income) (P < 0.001) in compensation for fair rather than good working relationships with staff, and £6500 (11% of net income) (P < 0.001) to compensate them for a shortage of staff. The least important characteristic was hours of work, with £562 per year (0.9% of their net income) (P < 0.001) required to induce consultants to work one extra hour per week. These preferences also varied among specific subgroups of consultants. Conclusions Important information on consultants' strength of preferences for characteristics of their job should be used to help to address recruitment and retention problems. Consultants would require increased payment to cover more intensive on-call commitments. Other aspects of working conditions would require smaller increases.